2022
DOI: 10.3390/su14042453
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Assignment of Egyptian Ornamental Stones for Interior and Exterior Building Finishes Using the AHP-TOPSIS Technique

Abstract: The ornamental stones industry has grown progressively in Egypt as the demand has increased for Egyptian decorative stones in indoor and outdoor building spaces. Choosing the most suitable ornamental stone for each purpose and taking the right decisions related to aesthetic and practical performance can be a challenge causing a lot of confusion for homeowners and contractors. Thus, there is a need to define what decorative style you are trying to achieve in order to properly choose the most suitable decorative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…The AHP-TOPSIS technique was employed by Ahmed et al to identify the sorts of stones that contribute to economic, environmental, and sustainable development. The study's findings revealed that stones that are ideal for use as building materials should have superior usability, physical qualities, and decorative look [48]; we contend that this research methodology places too much emphasis on theoretical application, whereas, in reality, consumer behavior can clarify which stone has better physical characteristics and aesthetic adornment. The surface roughness, color, and texture of marble samples can have a significant impact on visual imagery studies [46].…”
Section: Visual Imagery Evaluation Methodsmentioning
confidence: 92%
“…The AHP-TOPSIS technique was employed by Ahmed et al to identify the sorts of stones that contribute to economic, environmental, and sustainable development. The study's findings revealed that stones that are ideal for use as building materials should have superior usability, physical qualities, and decorative look [48]; we contend that this research methodology places too much emphasis on theoretical application, whereas, in reality, consumer behavior can clarify which stone has better physical characteristics and aesthetic adornment. The surface roughness, color, and texture of marble samples can have a significant impact on visual imagery studies [46].…”
Section: Visual Imagery Evaluation Methodsmentioning
confidence: 92%
“…On the other hand, the durability and attractiveness of ornamental stones make them eligible to be among the best alternatives for designing construction, building and other engineering projects [3,7].…”
Section: Of 17mentioning
confidence: 99%
“…Selecting the appropriate rock type for relative engineering purposes and making an exact decision regarding its usability and employability can be challenging and require effort on the part of homeowners and contractors [3]. For this purpose, developing maintenance-free buildings is highly desirable and, perhaps, an increasingly technical possibility, but hardly an achievable goal.…”
Section: Of 17mentioning
confidence: 99%
See 1 more Smart Citation
“…To solve the problem of different trends of data indicators, the identification and normalization of indicator trends were carried out. There are four indicator trend types, as shown in Table 1 [16].…”
Section: Multi-algorithm Constrained Modelmentioning
confidence: 99%